2002
DOI: 10.1023/a:1020517319363
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The presence of an alarm pheromone was demonstrated in the deutonymphal stage of the oribatid mite, Nothruspalustris (C. L. Koch). The active principle was identified as 3,7-dimethyl-(E)-2,6-octadienal, geranial, and was shown to be active at doses of 10-100 ng. This is the first such pheromone identified in oribatid mites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 1 publication
3
11
0
Order By: Relevance
“…Nerol and neryl propionate have not been found in the headspace of D. pteronyssinus so far. Interestingly, no volatiles were found in the headspace of tritonymphs, supporting the idea that the release of pheromones in D. pteronyssinus is stage specific, as has been reported also for other mite species [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Nerol and neryl propionate have not been found in the headspace of D. pteronyssinus so far. Interestingly, no volatiles were found in the headspace of tritonymphs, supporting the idea that the release of pheromones in D. pteronyssinus is stage specific, as has been reported also for other mite species [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, studies with house dust mites so far only addressed pheromone release and reaction to pheromones in adult mites while the role of pheromones for nymphs remained unclear. The characteristic opisthosomal glands (“oil glands”), which are made responsible for the release of most pheromones in astigmatid mites [ 5 ] are present in nymphs as well [ 12 ] and they have also been reported to release pheromones [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their food generally consists of decaying higher plant material and saprophytic fungi (31,32), although stable isotope studies indicate that necrophagy or predation on small invertebrates is common, especially in tropical soils (32,33). Oribatid mites posses paired exocrine glands (34), called opisthonotal or oil glands, that secrete a wide range of organic compounds, including monoterpenes, sesquiterpenes, aromatics, aliphatic aldehydes, a ketone, fatty acids, fatty acid esters, an alkyl formate, and hydrocarbons (12,(35)(36)(37)(38)(39)(40)(41)(42). The functions of these compounds have been little studied but include alarm signals and chemical defenses (34,38).…”
Section: Ecologymentioning
confidence: 99%
“…Oribatid mites posses paired exocrine glands (34), called opisthonotal or oil glands, that secrete a wide range of organic compounds, including monoterpenes, sesquiterpenes, aromatics, aliphatic aldehydes, a ketone, fatty acids, fatty acid esters, an alkyl formate, and hydrocarbons (12,(35)(36)(37)(38)(39)(40)(41)(42). The functions of these compounds have been little studied but include alarm signals and chemical defenses (34,38). In the better-studied and closely related mite group Astigmata (not occurring in our samples), compounds from homologous glands also function as aggregation signals and sex pheromones (40).…”
Section: Ecologymentioning
confidence: 99%
“…In fact, it has been shown that oribatid exocrine secretions-though only known from a small number of species for the time being-play an unexpectedly important role in their life and survival strategies. These secretions serve a variety of functions, comprising microbial and fungal protection, chemically-mediated predator defence or intraspecific communication by pheromones (Shimano et al 2002;Raspotnig 2006a). Besides semiochemical properties, exocrine secretions of oribatids are also considered involved in building up secretion layers on the cuticular surface.…”
Section: Introductionmentioning
confidence: 99%